Rainfall Analysis at the oil palm are Kebun PTP. Nusantara II Tanjung Garbus with water balance model) - Candra Kirana; Sumono Sumono; Najif Ichwan (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Oil palm plantation is rumoured as the main causes of deforestation, various damages of biodiversity and too much water consumption, therefore a research is needed with water balance model to arrange and analyze rainfall parameters as a water source at Kebun PTP. Nusantara II Tanjung Garbus, which carried out from April to July 2013. Water balance model consist of rainfall, throughfall, stemflow, interception, actual evapotranspiration and surface runoff. The result showed that the soil at the site was entisols with effective depth of 78 cm, sandy loam soil texture, bulk density of 1,363 g/cm3, particle density of 2,639 g/cm3, porosity of 48% and soil organic matter of 2,67%. The recent actual evapotranspiration during research was 99,039 mm/month whereas rainfall at the period was an average of 57,1 mm/month and becaming throughfall and stemflow of 45,397 mm/month, the interception was 11,72 mm/month and the surface run off was 0 mm/month. Height of ground water during 4 months research was 159,8 mm and in field capacity was 321,36 mm, so that 161,56 mm water deficit occurred. Based on 10 years annual rainfall of BMKG at the same months, the average of rainfall was 115/month. Key Words: rainfall, oil palm, water balance, water deficit